Silencing of E-cadherin expression leads to increased chemosensitivity to irinotecan and oxaliplatin in colorectal cancer cell lines. (December 2021) - Skarkova, Veronika; Skarka, Adam; Manethova, Monika; Stefanidi, Afroditi A; Rudolf, Emil
Colorectal carcinoma (CRC) is a leading malignant disease in most developed countries. In advanced stages it presents with metastatic dissemination and significant chemoresistance. Despite intensive studies, no convincing evidence has been published concerning the association of cadherins and epithelial-mesenchymal transition (EMT) as a direct cause of acquired chemoresistance in CRC. The present study was designed to investigate the role of E-cadherin in EMT and its associated chemosensitivity/chemoresistance in four immortalized CRC cell lines representing various stages of CRC development (i.e. HT29 and Caco-2—early, SW480 and SW620 late). The expression of E-cadherin gene CDH1 was downregulated by the specific siRNA. Cell proliferation and chemosensitivity to irinotecan (IT) and oxaliplatin (OPT) were detected using WST-1 and x-CELLigence Real Time analysis. Expression of selected EMT markers were tested and compared using RT-PCR and western blot analysis in both variants (E-cadherin silenced and non-silenced) of each cell line. We have discovered that downregulation of E-cadherin expression has a diverse effect on both cell proliferation as well as the expression of EMT markers in individual tested CRC cell lines, with Caco-2 cells being the most responsive. On the other hand, reduced E-cadherin expression resulted in increased sensitivity of all cell lines to IT and mostly to OPT which might be related to changes in intracellular metabolism of these drugs. These results suggest dichotomy of E-cadherin involvement in the phenotypic EMT spectrum of CRC and warrants further mechanistic studies.